Measuring plasma C4D to monitor immune complexes in lupus nephritis - Tineke Kraaij; Sara C. Nilsson; Cees van Kooten; Marcin Okrój; Anna M Blom; YK Onno Teng (Lupus Science and Medicine)
Objective Because currently available assays that measure circulating immune complexes (ICx) are suboptimal, a novel assay was recently developed measuring C4d, a stable product of activation of the classical complement pathway. The present study aimed to establish the value of measuring plasma C4d levels in a longitudinal cohort of patients with severe refractory SLE who were treated with a combination therapy of rituximab with belimumab (RTX+BLM).Methods Fifteen patients with SLE who were treated with RTX+BLM in a phase 2A, open label study were included to sequentially measure plasma C4d levels and correlated to well-established markers of ICx-formation, that is, autoantibodies against double-stranded (ds) DNA, autoantibodies against C1q and proteinuria. The performance of plasma C4d measurements, C4 measurements and the ratio of C4d over C4 (C4d:C4) was evaluated.Results After establishing that on RTX+BLM treatment kinetics of C4d levels was distinct from traditional C3 and C4 levels, we found strong correlation of C4d:C4 with anti-dsDNA (R=0.76, p<0.001) and anti-C1q (R=0.65, p<0.001) autoantibody levels, which outperformed both stand-alone C4 and C4d levels. Additionally, changes in C4d:C4 over time correlated strongly with changes in proteinuria (R=0.59, p<0.001) as well as anti-dsDNA (R=0.46, p=0.003) and anti-C1q (R=0.47, p=0.002).Conclusion In patients with severe SLE, plasma C4d levels in relation to C4 levels is useful for longitudinal monitoring after RTX+BLM treatment to reflect amelioration of classical complement activation by ICx as well as proteinuria.